# Assistance is needed.

Printable View

• Oct 8th 2008, 06:29 AM
gedprep
Assistance is needed.
n
2=n+1

can you help me solve this?
• Oct 8th 2008, 06:45 AM
masters
Quote:

Originally Posted by gedprep
n
2=n+1

can you help me solve this?

This is an addition equation because a value has been added to the variable n.
To isolate the variable (get the variable by itself on one side of the equation),
you must perform the inverse of addition (subtraction) on the value.

$2=n+1$

Subtract 1 from both sides

$2-1=n+1-1$

$1=n$

$\boxed{n=1}$
• Oct 8th 2008, 06:51 AM
gedprep
I made a mistake.
I am sorry but tis was 2 over n equals n plus 1
• Oct 8th 2008, 07:03 AM
masters
Quote:

Originally Posted by gedprep
I am sorry but tis was 2 over n equals n plus 1

$\frac{2}{n}=n+1$

First, multiply each term by n

$2=n^2+n$

Now, set the equation = 0

$n^2+n-2=0$

Now, factor the trinomial

$(n+2)(n-1)=0$

Using the zero product property that says "If ab=0, then a=0 or b=0",

$n+2=0 \ \ or \ \ n-1=0$

$n=-2 \ \ or \ \ n=1$
• Oct 8th 2008, 08:36 AM
gedprep
That error is my fault and I corrected it already. Check it out
I am sorry but it is n over 2 equals n plus 1

not 2 over n
• Oct 8th 2008, 08:47 AM
masters
Quote:

Originally Posted by gedprep
I am sorry but it is n over 2 equals n plus 1

not 2 over n

Third time's the charm...

$\frac{n}{2}=n+1$

Multiply all terms by 2 (in order to eliminate the fraction)

$n=2n+2$

Subtract 2n from each side.

$-n=2$

Multiply everything by -1.

$n=-2$
• Oct 8th 2008, 08:56 AM
gedprep
Re: Assistance is needed
why must you multiply the 1 as well as the number n?
• Oct 8th 2008, 09:46 AM
masters
Quote:

Originally Posted by gedprep
why must you multiply the 1 as well as the number n?

One of the 10 commandants of math is:

Thou shalt do unto one side of an equation what thou doest to the other.

If I multiply 2 times one term in an equation, I must multiply 2 times every term in the equation.

Example:

$\frac{x}{2}+3=2x-1$

Multiple all terms by 2.

${\color{red}2}\left(\frac{x}{2}\right)+{\color{red }2}(3)={\color{red}2}(2x)-{\color{red}2}(1)$